Management Of The Internal Quality Assurance System (Iqas) In Improving The Quality Of Higher Graduates - Pujiati, Herni; Wasliman, Iim; Tutty, Ade; Andriana Gaffar, M. (International Journal of Science, Technology & Management, 2022)
This paper aims to describe the other side of the management of the internal quality assurance system (IQAS) in improving the quality of university graduates. Quality improvement management based on university graduates is a new alternative in education management which emphasizes more on independence and creativity. The development of the quality assurance system management is designed to improve the community's ability to manage educational change in relation to the overall objectives, policies, planning strategies, curriculum initiatives that have been determined by the government and education authorities. Therefore, the output of education demands a change in the attitudes and behavior of all components that involve all people, both the community, in viewing, understanding, helping as well as observers who carry out monitoring and evaluation. This study uses a descriptive analysis method approach. A method approach that is used to analyze, describe and summarize various conditions, and situations from various data collected from observations regarding the problem under study during the research. The problem of the low quality of higher education is the reason for the government to provide a policy by presenting an internal quality assurance system (IQAS) in universities. The internal quality assurance system (IQAS) is managed independently by the university concerned. Then in the management of higher education quality is carried out on an ongoing basis. This study aims to analyze the role of the internal quality assurance system (IQAS) in improving the quality of higher education.